Martin of Cochem’s Golden Key of Heaven and its Czech Relatives: Quantitative Analysis of Baroque Prayers - KUBÁT, Miroslav; NETOLICKÁ, Šárka; ČECH, Radek; MAČUTEK, Jan (Bohemistyka, 2021)
Rewriting books was a widespread phenomenon during the Baroque period of the Czech literature. The manuscripts were not always „honest copies”, on the contrary, scribes often compiled several sources or added their own texts to the original. The famous book Golden Key of Heaven by Martin of Cochem is compared with a manuscript Key of Heaven from a Regional museum in the town of Náchod. We use two statistical methods, both of them strongly indicate that the manuscript is a copy of some chapters from the Golden Key of Heaven rather than a compilation.